EN ISO 15189 revision: EFLM Committee Accreditation and ISO/CEN standards (C: A/ISO) analysis and general remarks on the changes - Linko, Solveig; Boursier, Guilaine; Bernabeu-Andreu, Francisco A; Dzneladze, Nana; Vanstapel, Florent; Brguljan, Pika Meško; Tosheska-Trajkovska, Katerina; Mehay, Hélène; Panteghini, Mauro; Brugnoni, Duilio; Milinkovic, Neda; Lohmander, Maria; et al. (Clinical chemistry and laboratory medicine, 2025)
The EN ISO 15189:2022 standard, titled "Medical laboratories - Requirements for quality and competence," is a significant update to the regulations for medical laboratories. The revised standard was published on December 6, 2022, replacing both EN ISO 15189:2012 and EN ISO 22870:2016. Key objectives of the revision include: 1. Alignment with ISO/IEC 17025:2017, 2. Removal of unintended prescription, 3. Focus on patient interest and safety, 4. Minimization of new requirements, and 5. Improved clarity of text. Dedicating to harmonizing accreditation processes across Europe the EFLM Committee on Accreditation and ISO/CEN standards (C: A/ISO) has produced this guidance document to assist the laboratory medicine community in understanding and implementing the criteria of the EN ISO 15189 revision. Two main objectives of the guidance in educating both laboratories and accreditation bodies with their assessors as well as other stakeholders in laboratory medicine were agreed on. Firstly, to clarify the relevant changes covering all paragraphs of the standard and secondly to make an impact analysis on previous C: A/ISO guidance documents.
Keywords: laboratoře; Accreditation; accreditation; klinické laboratoře; lidé; akreditace; Europe; Evropa; Laboratories, Clinical; perspective; Laboratories; EN ISO 15189; EN ISO 22870; Humans